In vivo Biocompatibility and Bioactivity of Calcium Silicate-Based Bioceramics in Endodontics - Wencheng Song (Frontiers in Bioengineering and Biotechnology, 2020)
Endodontic therapy aims to preserve or repair the activity and function of pulp and periapical tissues. Due to their excellent biological features, a substantial number of calcium silicate-based bioceramics have been introduced into endodontics and simultaneously increased the success rate of endodontic treatment. The present manuscript describes the in vivo biocompatibility and bioactivity of four types of calcium silicate-based bioceramics in endodontics.